Reduction Levels of Copper (Cu) Electrolysis Method In Priting Liquid Waste Processing Circuit Board (PCB) - Silfi Arini; Bambang Suharto; Liliya Dewi S.; Handaru B Cahyono (Jurnal Sumberdaya Alam dan Lingkungan, 2017)
Electronics industry is one of the national priorities industry continues to grow and evolve. National electronics industry growth of 10.9% and export value of US $ 9.084 billion, second only to the export of textile (Textile Products Textile) and an average production rate of 65-70%. Some of the electronic components industry also contributed to the growth of one PCB. Based on B3 material content is high, especially in the waste solution soaked concentrated liquid PCBs or PCB industry, the liquid waste must be performed prior to treatment of wastewater released into envinronment.. This method is used by electrolysis with 7.5 Volt. Type of this research is a laboratory experiment. This sample form elektrodaposisi copper (Cu) by passing electric current to the electrodes are dipped in liquid waste (process etcing) PCB manufacture. The approach used in this research is a quantitative approach and using mathematical analysis, with the intention of analyzing the data that is expressed with nominal. Quantitative data were obtained from the variation of the duration of the process, the distance between the electrodes, and the type of electrode used then the data will be derived using mathematical formulas. Based on the research results, Copper (Cu) were dissolved in the liquid waste PCB may be copper deposit with the removal of 70% - 90%. The electrodes that provide high efficiency at elektrodaposisi copper (Cu) in the wastewater industry PCB is a steel plate with at a distance of 1 cm. Based on the results of this steel plate decreased 88% removal. The time between the electrodes required to process elektrodaposisi copper (Cu) in the wastewater industry PCBs at 60 minutes, This is done because there is no longer a significant increase occurred in the copper deposit at the cathode. Mass of copper in the electrolyte solution has been nearly exhausted in the mass.Keywords: Electrolysis method, Liquid waste PCB, Reduction of the levels of processing copper (Cu).